Characterization of the Baobab fruit shells as adsorption material - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Alam, Md Zahangir; Qudsieh, Sam Yassin; Bello, Ibrahim Adebayo (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
The Baobab (Adansonia digitata L.) is a large iconic tree indigenous to Africa where it is found in many countries. The Baobab tree has various uses, as it produces food and non-food products such as medicines, fuel, timber and fodder. This research is focused on the characterization of the Baobab fruit shells in terms of lignin (54.08%), cellulose (24.87%) and hemicellulose (21.05%) content, as well as proximate analysis such as ash content (5.17%), moisture content (6.48%), volatile matter (86.73%) and carbon content (1.22%). This assessment will play a vital role in exploring the benefits of utilizing baobab fruit shells in the production of activated carbon as well as set a foundation for future research.